Fatigue Test of Plastics and Manufacturing Collet Nut Driver for Integrated Rotating Bending Fatigue Test Machine - Tri Setyo Aji Cahyono; Syamsul Hadi; Rico Wahyu Pratama; Zakiyah Amalia; Fica Aida Nadhifatul Aini; Aini Zuhra Binti Abdul Kadir (Logic : Jurnal Rancang Bangun dan Teknologi, 2024)
The unknown fatigue life of injection molded plastic materials and the ineffectiveness of clamping both ends of the specimen in the collet of the Integrated Rotary Bending Fatigue Testing Machine with manual tightening and loosening are the obstacles faced. The purpose of testing and making a collet nut driver is to obtain a prediction of the fatigue life of injection molded plastic materials and to increase the effectiveness of clamping the end of the specimen with the help of a DC motor drive. The research method uses experiments which include injection molding of plastic materials of the type Polypropylene (PP) and Acrylonitrile Butadiene Styrene (ABS), checking the straightness and surface finishing of the specimen, fatigue testing at 1800, 2000, 2200 rpm, analysis of fatigue test results, and design-manufacturing collet nut drive with DC motor drive and transmission of a pair of spiral cone gears, manufacture of DC motor sliding movement mechanism along the reach of both ends of the specimen, installation of electric power circuits for direction and electric current switches for clockwise and counterclockwise rotation functions, and analysis of the results of the fatigue test and performance of the collet nut driver The results of fatigue testing at a bending stress (S) of 68 MPa for PP material show that at 1800 rpm, the fatigue life (N) was obtained at 2,014,605 cycles and at 2200 rpm, N was obtained at 1,506,486 cycles. Meanwhile, for ABS specimens, at 1800 rpm, N was obtained at 1,547,106 cycles and at 2200 rpm, N was obtained at 1,190,425 cycles, which means PP material has a longer fatigue life compared to ABS. The test results of the DC motor drive on the collet nut showed that the duration of tightening/loosening was 4.4 times faster than manually, which originally had a duration of 66 seconds, down to just 15 seconds for the DC motor drive.